The effectiveness of oil palm shell (OPS) as major aggregate replacement in concrete - N., Abdul Rahman*; Tan, A.S.H; F., Waqbitu; N.H., Roslan (IOP Publishing, 2020)
Malaysia known as one of global leaders in production and export of palm oil. This huge production of palm oil has produced high waste product which might cause to environmental pollution. The aim of this study is to determine the effectiveness of oil palm shell (OPS) as aggregate replacement in concrete and at the same time help to reduce the environmental pollution. The workability, density, and strength performances of concrete incorporated with 80% of OPS as coarse aggregate replacement were being investigated. Through the experimental test has shown that the OPS have high potential to be used as aggregate replacement in concrete. Furthermore, the experimental test results exhibited the advantage of OPS in reducing the density of concrete within 1800kg/m3 to 2000 kg/m3. However, the compressive strength of concrete containing OPS was decreased up to 35% from normal concrete strength. Thus, by introducing steel fibres into the OPS concrete has help in improving the concrete strength. Hence the additional of steel fibre into concrete has shown good potential in improving the lightweight concrete since it shows lower in density and 35% higher than minimum lightweight concrete strength as stated by ASTM C330-89.